Preoperative and Postoperative Midline Index Ratio and Pre- and Postoperative Variation of the Hematoma Thickness Accurately Predict Surgical Recurrence of Chronic Subdural Hematomas - Novegno, Federica; Fiorucci, Giulia; Iaquinandi, Andrea; Salvati, Maurizio; Pesce, Alessandro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Chronic subdural hematoma (cSDH) is a common pathology in daily practice of neurosurgery. Surgical management usually offers a significant clinical recovery. However, the recurrence rate is still high. Several studies have suggested various factors associated with hematoma recurrence with no univocal results. The aim of this study was to determine the prognostic value of early postoperative computed tomography (CT) examination to predict the need for reoperation.Methods A retrospective review of 115 cSDH patients was performed. Clinical findings and pre- and early postoperative CT scan data were recorded. Univariable and bivariable analyses were performed to determine which of the studied factors were associated with an increased risk of reoperation. Their prognostic abilities were assessed using receiver operating characteristic curves.Results Overall, 21 of 115 patients required a surgical revision. Among the comorbidities, diabetes mellitus represented the only factor related with hematoma recurrence (66.76 vs. 23.40%, p = 0.001). Preoperative hematoma density and postoperative residual hyperdensity on early CT scan emerged as significant predictors of cSDH recurrence (recurrence: 18/21, 85.7% vs. nonrecurrence: 17/94, 18.1%, p = 0.001). The ratios of post- and preoperative hematoma thickness (P) and post- and preoperative midline shift (Q) and their sum (K) were statistically higher in the recurrence group with cutoff values of 0.745, 0.555, and 1.135, respectively.Conclusions Systematic early postoperative CT scan after cSDH evacuation may predict hematoma recurrence. In the present study, we found postoperative hyperdensity on CT scan and degree of hematoma variation after surgical evacuation to be the strongest predictors of the need for reoperation.
Keywords: chronic subdural hematoma; recurrence; computed tomography; surgery